nab-Paclitaxel–Based Therapy in Underserved Patient Populations: The ABOUND.PS2 Study in Patients With NSCLC and a Performance Status of 2 - Gajra, Ajeet (Front Oncol, 2018)
INTRODUCTION: The phase II ABOUND.PS2 study (NCT02289456) assessed safety/tolerability of a first-line modified nab-paclitaxel/carboplatin regimen for patients with advanced non-small cell lung cancer (NSCLC) and Eastern Cooperative Oncology Group (ECOG) performance status (PS) 2. METHODS: Chemotherapy-naive patients with stage IIIB/IV NSCLC and ECOG PS 2 received four cycles of nab-paclitaxel 100 mg/m(2) days 1 and 8 plus carboplatin area under the curve 5 day 1 q3w (induction). Patients without progression received nab-paclitaxel monotherapy (100 mg/m(2) days 1 and 8 q3w) until progression/unacceptable toxicity. Primary endpoint: percentage of patients discontinuing induction due to treatment-emergent adverse events (TEAEs). RESULTS: 11/40 treated patients (27.5%; 95% CI, 14.60–43.89) discontinued chemotherapy induction due to TEAEs; 16/40 (40.0%) continued nab-paclitaxel monotherapy. Median progression-free and overall survival were 4.4 (95% CI, 2.99–7.00) and 7.7 (95% CI, 4.93–13.17) months. Grade 3/4 TEAEs during induction included neutropenia (22.5%), anemia (17.5%), thrombocytopenia (5.0%), and peripheral neuropathy (2.5%). CONCLUSION: This nab-paclitaxel–based regimen was tolerable in patients with advanced NSCLC and ECOG PS 2, with efficacy comparable to historical chemotherapy data.